Determinants of social performance efficiency of ESG and Non-ESG firms: evidence from Southeast Asian countries - Ali, Muhammad Hafiz; Abdul Rahim, Norhuda; Yahya, Mohamed Hisham; Kamarudin, Fakarudin (UiTM Press, 2022)
The skewed research attention of past literature relatively failed to emphasize on the true objective of firms’ social responsibility; which is upholding stakeholders’ wellbeing. Hence, this study investigated the efficiency of firms in giving back to the masses. Primarily, this study examined firms’ social performance (SP) efficiency by using Data Envelopment Analysis (DEA). Next, by using Panel Regression Analysis; this study investigated the determinants of SP efficiency (internally and externally), based on Institutional Theory. The study focused on both ESG and non-ESG firms in Malaysia and Singapore from 2010 to 2019. First, novelties on SP efficiency are that both countries’ ESG firms are far more efficient in giving back to the masses, compared to non-ESG firms. Additionally, firms’ SP efficiency is significantly influenced by firm’s pure technical inefficiency in directing their financial returns toward ESG contribution. Second, for determinants of SP efficiency; the study yielded findings that are unique to each country. Both firm characteristics (internal) and country characteristics (external) had a significant influence of Malaysia’s ESG firms. While, only country characteristics were significant influence of Singapore’s ESG firms. Moreover, only firm characteristics were found to be significant predictors of SP efficiency for both countries’ non-ESG firms.